Upaya Meningkatkan Perkembangan Kognitif Anak Melalui Permainan Ular Tangga Kelompok B Di RA Perwanida Muara Enim Tahun 2021 - Putri; Leny Marlina; Fahmi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study entitled "Efforts to Improve Children's Cognitive Development Through Snakes and Ladders Game Group B at RA Perwanida Muara Enim. The background of this research is the lack of children's cognitive development when learning along with their age development. The formulation of the problem in this study is how the process of improving children's cognitive development through the game of snakes and ladders at RA Perwanida Muara Enim. The goal is that children are able to have readiness to enter further education. This research is a classroom action research that uses the research design of Kemmi & McTaggart which consists of planning, observing and reflecting. There were two (2) cycles that were applied, each cycle consisting of three meetings. The data collection technique used is field note observation, interview notes, and documentation notes. The results of this study indicate that there is an increase in children's cognitive development through the game of snakes and ladders at RA Perwanida Muara Enim. This is evidenced by the overall score on pre-cycle activities with a score of 539 (23.00) with a percentage of 12% (3:25x100). Then in the first cycle activities as a whole got a score of 739 (30.00) with a percentage of 48% (12:25x100), and the last in the second cycle as a whole got a score of 1,249 (50.00) with a percentage of 80% (20:25x100) . So that this research is said to be successful, because the percentage of children's cognitive development reaches 80% while the minimum percentage is 75%.